1997
DOI: 10.1111/j.1439-0507.1997.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to fluconazole and itraconazole of Candida spp. in denture stomatitis

Abstract: The significance of Candida albicans in the development of denture stomatitis (DS), as well as the clinical and microbiological efficacy of treatment with fluconazole and itraconazole was studied in 115 patients affected with DS and 200 controls (100 healthy patients with dental prosthesis and 100 healthy patients without prosthesis). Specimens were taken from all patients; subsequently all patients with positive culture of the DS group were treated with fluconazole. A second specimen was taken after 15 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Uncontrolled trials have reported capsule and liquid formulations of itraconazole (100 mg b.i.d. for 15 days), fluconazole alone (50 mg orally for 14 days), or in combination with chlorhexidine applied to the denture fitting surface twice daily for 2 weeks, and amphotericin (40 mg oral dissolving lozenges 4 times daily + topical cream applied to the denture fitting surface) all to be efficacious for treating denture stomatitis 70–73 . In general, all studies indicated the various treatments to be well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Uncontrolled trials have reported capsule and liquid formulations of itraconazole (100 mg b.i.d. for 15 days), fluconazole alone (50 mg orally for 14 days), or in combination with chlorhexidine applied to the denture fitting surface twice daily for 2 weeks, and amphotericin (40 mg oral dissolving lozenges 4 times daily + topical cream applied to the denture fitting surface) all to be efficacious for treating denture stomatitis 70–73 . In general, all studies indicated the various treatments to be well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to remember that the majority of data used to establish interpretative breakpoints in the NCCLS protocol were collected from either AIDS or candidemia patients (28, 29). We found only one study in the literature which correlated in vitro susceptibility testing and clinical findings in immunocompetent patients with oral candidiasis (20). In the study, researchers found 1 in vitro fluconazole‐resistant strain of C. albicans out of 78 strains obtained from patients with clinical signs of infection positive fungal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Fluconazole‐resistant oral candidiasis in healthy outpatients has not been extensively studied. To our knowledge, only two reports have been published describing in vitro antifungal susceptibility testing done in oral C. albicans isolates in non‐AIDS patients (19, 20). As the use of fluconazole for the treatment of oral candidiasis has become widespread in the immunocompetent patient population, it is important to determine the prevalence of fluconazole‐resistant strains of C. albicans in these patients so that clinicians can administer the most effective treatment.…”
mentioning
confidence: 99%
“…Although azole derivates are known to be effective, long‐term use may cause changes in enzymes of the liver. Additionally, fluconazole has some systemic adverse effects including headaches, skin rash, vomiting, abdominal pain and diarrhea (Bissell et al , 1993; Bennet, 1996; Martin Mazuleos et al , 1997; Cross et al , 1998).…”
Section: Discussionmentioning
confidence: 99%